Growth of Nanocrystalline MoSe2 Monolayers on Epitaxial Graphene from Amorphous Precursors (Phys. Status Solidi B 2/2019). Issue 2 (15th February 2019) - Göhler, Fabian; Hadland, Erik C.; Schmidt, Constance; Zahn, Dietrich R. T.; Speck, Florian; Johnson, David C.; Seyller, Thomas
Abstract : On the back cover a new approach to grow monolayers of MoSe2 is illustrated. In a first step, an amorphous precursor is deposited on a substrate, in this case epitaxial graphene on silicon carbide. In a second step, nano‐crystalline MoS2 in randomly oriented domains self‐assembles upon annealing. Films with a thickness of one monolayer were successfully grown, as was demonstrated by characterization using a variety of techniques. This approach opens up an avenue to synthesize a number of new van‐der‐Waals systems on epitaxial graphene and other substrates. Further details can be found in article number 1800283 by Fabian Göhler et al.